Novel CuCo2O4 Composite Spinel with a Meso-Macroporous Nanosheet Structure for Sulfate Radical Formation and Benzophenone-4 Degradation: Interface Reaction, Degradation Pathway, and DFT Calculation - Yiping Wang; Ji, Haodong; Liu, Wen; Xue, Tianshan; Liu, Chao; Yuting Zhang; Liu, Longyan; Qiang Wang; Fei Qi; Bingbing Xu; Tsang, Daniel C. W.; Chu, Wei (ACS Applied Materials & Interfaces, 2020)
A series of CuCo2O4 composite spinels with an interconnected meso-macroporous nanosheet morphology were synthesized using the hydrothermal method and subsequent calcination treatment to activate peroxymonosulfate (PMS) for benzophenone-4 (BP-4) degradation. As-prepared CuCo2O4 composite spinels, especially CuCo-H3 prepared by adding cetyltrimethylammonium bromide, showed superior reactivity for PMS activation. In a typical reaction, BP-4 (10.0 mg/L) was almost completely degraded in 15 min by the activation of PMS (200.0 mg/L) using CuCo-H3 (100.0 mg/L), with only 9.2 μg/L cobalt leaching detected. Even after being used six times, the performance was not influenced by the lower leaching of ions and surface-absorbed intermediates. The possible interface mechanism of PMS activation by CuCo-H3 was proposed, wherein a unique interconnected meso-macroporous nanosheet structure, strong interactions between copper and cobalt, and cycling of Co(II)/Co(III) and Cu(I)/Cu(II) effectively facilitated PMS activation to generate SO4•– and •OH, which contributed to BP-4 degradation. Furthermore, combined with intermediates detected by liquid chromatography quadrupole time-of-flight mass spectrometry and density functional theory calculation results, the degradation pathway of BP-4 involving hydroxylation and C–C bond cleavage was proposed.